Daily consumption of white tea (Camellia sinensis (L.)) improves the cerebral cortex metabolic and oxidative profile in prediabetic Wistar rats. Issue 5 (26th February 2015) - Nunes, Ana R.; Alves, Marco G.; Tomás, Gonçalo D.; Conde, Vanessa R.; Cristóvão, Ana C.; Moreira, Paula I.; Oliveira, Pedro F.; Silva, Branca M.
Abstract : Diabetes mellitus (DM) is a major public health problem and its incidence is rising dramatically. The brain, particularly the cerebral cortex, is very susceptible to glucose fluctuations and hyperglycaemia-induced oxidative stress. Tea ( Camellia sinensis (L.)) is widely consumed; however, the antidiabetic properties of white tea remain largely unexplored. In the present study, we investigated the effects of daily consumption of white tea on the cerebral cortex of prediabetic rats. The cerebral cortex metabolic profile was evaluated, and the expression levels of GLUT, phosphofructokinase-1, lactate dehydrogenase (LDH) and monocarboxylate transporter 4 were assessed. LDH activity was also determined. The cerebral cortex oxidative profile was determined by evaluating its antioxidant power, lipid peroxidation and protein oxidation levels. Catalase, glutathione, glutamate, N -acetylaspartate, aspartate, choline, γ-aminobutyric acid, taurine and valine contents were determined. Daily consumption of white tea ameliorated glucose tolerance and insulin sensitivity. Moreover, white tea altered the cortex glycolytic profile, modulating GLUT expression and lactate and alanine contents. Finally, white tea consumption restored protein oxidation and lipid peroxidation levels and catalase expression, and improved antioxidant capacity. In conclusion, daily consumption of white tea improved the cerebral cortex metabolic and oxidative profile in prediabetic rats, suggesting it as a good, safe and inexpensive strategy to prevent DM-related effects in the cerebral cortex.